The Venture Bros. : season 4, vol. 1 [videorecording (DVD)] - Urbaniak, James, 1963-; Warburton, Patrick; Sinterniklaas, Michael (Warner Home Video, 2010)
Questions are answered and truths are revealed. Learn how Henchman 21 copes with life without 24. See what happens when Brock and the Venture family are forced to part ways. Discover the final fate of H.E.L.P.eR. And all the while, the balance of the free world hangs in the hands of Dean Venture, who must kill Hitler.